Bilateral Staged Total Hip Replacement and the Natural Progress of an Untreated Case of Developmental Dysplasia (Dislocation) of the Hip: A Clinical Case Report by the Surgeon and the Patient - Hamid Honarpisheh; Mohammad Taghi Ghazavi (Iranian Journal of Medical Sciences, 2015)
The natural history of an untreated case of a Developmental Dysplasia (Dislocation) of the Hip (DDH) associated with multiple congenital abnormalities is reported in a 55-years-old man. The patient’s complaints and the varieties of the typical manifestations emerged in other parts of the body throughout the life are reviewed and discussed as comorbidities of a dysplastic condition. Two-stage bilateral total hip replacement (THR) operations were performed at the age of 55. In addition, to relieve the pain, the walking disabilities were overcome, hence gaining normal walking in swing and stances. The leg length discrepancy was corrected by anatomically positioned prostheses, examined by the knee bending test and characterized and evidenced by radiological features and indices.